Globalization and Foreign Direct Investments - Maria - Ramona Sarbu (CES Working Papers, 2015)
Much discussed and analyzed globalization is a multidimensional and complex process having today a significant magnitude as compared to the past, manifested through various forms of internationalization of production, foreign direct investment (FDI) flows, transnational corporations (TNCs), technology transfers, capital movements, migration flows, amplifying competition between investors and the connections between markets. The complexity phenomenon of globalization contributes to the diversification of opportunities for the development of national economies through effects in economic, political, social, technological, cultural sphere, intensifying the economic and financial relationship between economies and the interdependence between them. The purpose of the current attempt of research is to analyze the link between FDI and globalization, the paper focusing on FDI as one of the most powerful evidence of economic globalization.
Keywords: E22; F21; P33; 330; globalization; FDI flows; TNCs